All intersectionality is not the same: Why Kamala Harris is our vice president and not Stacey Abrams. Issue 4 (2nd October 2021) - Locke, Thomas; Joseph, Ralina L.
ABSTRACT: In his campaign for president, Joseph R. Biden emerged as a frontrunner after pledging to select a vice president who has a different identity than his own. As the most loyal demographic for the Democratic Party, choosing a Black woman as a nominee for vice president challenges previous understandings of presidentiality. Pressure to select a Black woman vice president also exposes how intersectionality can differ in political decision-making, as Kamala Harris's version of intersectionality stands out to Biden compared to others. This article examines two performative events: Kamala Harris's election-night victory speech and Stacey Abrams's non-concession concession speech, to understand why Harris's brand of intersectionality, and not Abrams's, resonated more with the Biden campaign. Representing two different forms of intersectionality, both speeches centralize race and gender, shifting how we understand the 2020 presidential election alongside a long tradition of racial exclusion. As we reflect on the implications of the previous presidency, remarks from both Stacey Abrams and Kamala Harris remind us of the extent to which Black women have fought against a white supremacist system and how versions of intersectionality are not the same.